2023
DOI: 10.3390/v15091849
|View full text |Cite
|
Sign up to set email alerts
|

Viruses in Laboratory Drosophila and Their Impact on Host Gene Expression

Oumie Kuyateh,
Darren J. Obbard

Abstract: Drosophila melanogaster has one of the best characterized antiviral immune responses among invertebrates. However, relatively few easily transmitted natural virus isolates are available, and so many Drosophila experiments have been performed using artificial infection routes and artificial host–virus combinations. These may not reflect natural infections, especially for subtle phenotypes such as gene expression. Here, to explore the laboratory virus community and to better understand how natural virus infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 135 publications
0
3
0
Order By: Relevance
“…Persistent viral infections are common in arthropods and are known to be widespread in laboratory reared D. melanogaster , where Nora virus and DAV have reported prevalence of up to 52% and 18%, respectively 28 . Persistent viral infections are generally considered to pose no or only minor fitness costs for the host 27 , but there is relatively little published experimental data to support this claim and emerging studies demonstrate significant fitness impacts of persistent viral infection in D. melanogaster 90,91 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Persistent viral infections are common in arthropods and are known to be widespread in laboratory reared D. melanogaster , where Nora virus and DAV have reported prevalence of up to 52% and 18%, respectively 28 . Persistent viral infections are generally considered to pose no or only minor fitness costs for the host 27 , but there is relatively little published experimental data to support this claim and emerging studies demonstrate significant fitness impacts of persistent viral infection in D. melanogaster 90,91 .…”
Section: Discussionmentioning
confidence: 99%
“…Persistent viral infections are generally considered to pose no or only minor fitness costs for the host 27 , but there is relatively little published experimental data to support this claim and emerging studies demonstrate significant fitness impacts of persistent viral infection in D. melanogaster 90,91 . Moreover, re-analyses of published RNA-seq data from laboratory reared flies revealed previously undetected infections with several viruses including Nora virus, Thika virus, and DAV that induced significant changes in the host transcriptome 28,92 . Here we found that persistent infections with DAV, DCV, Nora virus, and Bloomfield virus all promote ISC proliferation and are associated with intestinal dysplasia (Figure S1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation